The dynamics of economic growth policy insights from comparative analyses in Asia - Khuong, Vu Minh.; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2013)
'Asia, like other continents outside Western Europe and North America, was poor and considered a least-hope region for breaking the poverty trap in post WWII. However, Asia has surprisingly become the most dynamically growing region in the world in the recent decades with extraordinary speed and scale. This book is an insightful study of the root causes and strategic policy framework of Asia's development success. It provides convincing analyses to show that other lower-income countries can learn useful lessons from Asia to achieve their aspiration for prosperity. The book is a must-read for all policy makers and students in the developing world and international development institutions.' - Justin Yifu Lin, Peking University, China and formerly Chief Economist and Senior Vice President of the World Bank. 'There are many studies that attempt to explain the rapid rise of the economies of East and South Asia. Only a few of these studies base their analysis on a systematic quantitative comparison of the sources of growth in East and South Asia and none do so with more rigor than this work by Professor Vu Minh Khuong. The study is a major contribution to our understanding of these important economies' performance.' - Dwight Perkins, Harvard Kennedy School, US. 'The astonishing rise of Asia over the past decades is transforming the world economy and changing the balances in global politics. In this book, Professor Vu Minh Khuong provides an in-depth study of the drivers of growth in sixteen Asian economies based on solid empirical analyses. While successful growth relies heavily on investment, technology catch-up and openness to trade, Professor Vu emphasizes the decisive importance of enlightened leadership that creates a favourable environment for countries to prosper.' - Marcel Timmer, University of Groningen, The Netherlands. 'Prof Vu's timely book provides an excellent analytical study of the growth dynamics in Developing Asia, against the backdrop of a secular shift in the centre of gravity of the global economy from the West to the East. Indeed, his careful attention to data issues and efforts to adapt the standard growth accounting methodology to the Asian context sets an important benchmark for studies in this field. The author's enunciation of a "strategic (growth) policy framework" with its critical elements of enhancing a country's absorptive capacity and incentives for investment efficiency, underscores the policy imperatives facing Developing Asia in the quest for sustainable and inclusive long-term growth. This book will prove an indispensable reference for policymakers.' - Edward S. Robinson, Monetary Authority of Singapore. 'This book gives the reader a three-in-one deal. First, a careful accounting for the building stones of Asia's dynamic growth performance. Second, a comprehensive assessment of the policy environment that have brought Asia's success to bear. And third, a detailed exposition of how growth accounts can be used as a complementary tool to current-day national accounting to diagnose, monitor and implement growth policies.' - Bart van Ark, The Conference Board, US and University of Groningen, The Netherlands. 'The sixteen countries of developing Asia studied in this book account for half of the world's population and more than a quarter of its GDP. Their spectacular growth over the last several decades is an unprecedented economic achievement that has lifted millions of people out of poverty. In this volume, Khuong Minh Vu brings together a wealth of data that allow for both an excellent overview of economic growth in the region and a decomposition of growth into its underlying drivers. The book provides a wealth of insights into the growth model that continues to power this remarkable economic transformation.' - David Weil, Brown University, US. The advancement of a nation from poverty to prosperity is not a technical process but a great transformation. At the center of this change are two driving forces - emotion, which is referred to as aspiration, anxiety, and sense of responsibility; and enlightenment, which is associated with the freedom from dogmatism, open-mindedness, and the hunger for learning. It is these two factors that have determined not only the remarkable success of Asia in economic development but also the uniqueness of its growth model. This book examines the rise of Asia in the past two decades and draws lessons from its growth patterns.
1. Introduction -- 2. Developing Asia in the global dynamics of catching up and falling behind -- 3. The rise of Asia -- 4. Sources of developing Asia's economic growth : insights from the standard growth accounting approach -- 5. Sustaining high economic growth in developing Asia : strategic insights and a catch-up policy framework.
Includes bibliographical references.
Keywords: Economic development -- Asia; Electronic books